Successful removal of a giant esophageal lipoma by thoracoscopic enucleation: a case report - Wataru Goto; Katsunobu Sakurai; Naoshi Kubo; Yutaka Tamamori; Kiyoshi Maeda; Masaichi Ohira (Surgical Case Reports, 2020)
Abstract Background We report a rare case of giant esophageal lipoma treated with thoracoscopic enucleation successfully. Case presentation A 69-year-old woman was referred to our department with dysphagia. Computed tomography examination revealed a large hypoattenuating submucosal mass with dense fat in the middle and lower esophagus. Upper gastrointestinal endoscopy revealed a submucosal mass with normal mucosa on the middle and lower esophageal wall. On a diagnosis of esophageal lipoma, we performed a video-assisted thoracoscopic operation and the 14.0 × 6.5 × 3.0 cm in size submucosal tumor was completely enucleated. We could successfully avoid a subtotal esophagectomy with high invasiveness. The patient was discharged on the 36th day after operation, and no symptoms had been noted. Conclusions Video-assisted thoracoscopic enucleation with minimal invasiveness may be an appropriate treatment option even for such a huge benign esophageal submucosal tumor.